2019
DOI: 10.18203/2320-1770.ijrcog20193018
|View full text |Cite
|
Sign up to set email alerts
|

Key predictors of modern contraceptive use among women in marital relationship in South-West region of Nigeria

Abstract: Background: Nigeria’s population is the seventh largest in the world and is projected to be the fourth largest by 2050. The demographic scenario is akin by persistent high fertility and low contraceptive use. This paper examined factors influencing contraceptive use among women in marital relationship in south-west region which has the highest percentage of use compared to other regions.Methods: A sub-sample of 3,784 women in marital relationship in the south-west region aged 15-49 was extracted from the 38,94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This aspect is important because the study observed that more than half of the single mothers had sexual contacts with casual friends. Also, the study reveal that modern contraceptive use increase with improvements in single mothers' household wealth quintile and employment in agreement with nding in previous studies [56][57][58][59][60] which provides support for the women empowerment strategies of the current national population policy [18]. It is expected that as women's economic power improves, their say in household decision-making may improve and more women may be able to access methods that are not covered by the free user fee initiative in public health facilities in the country.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This aspect is important because the study observed that more than half of the single mothers had sexual contacts with casual friends. Also, the study reveal that modern contraceptive use increase with improvements in single mothers' household wealth quintile and employment in agreement with nding in previous studies [56][57][58][59][60] which provides support for the women empowerment strategies of the current national population policy [18]. It is expected that as women's economic power improves, their say in household decision-making may improve and more women may be able to access methods that are not covered by the free user fee initiative in public health facilities in the country.…”
Section: Discussionsupporting
confidence: 90%
“…The demographic characteristics are age group (15-24, 25-34 and 35-49 years), age at sexual debut (less than 18 years or 18 or older), parity (one child, two-four children, and ve or more children) fertility desire (wanted more children or wanted no more), and child living arrangement (lives with mother or lives elsewhere). These variables are selected based on their signi cance in previous studies [33][34][56][57][58][59][60]. The control variables are nature of singlehood (premarital or post marital singlehood), sexual activity (active or inactive) and most recent sexual partner (boy/man friend, commercial worker and casual friends).…”
Section: Research Variablesmentioning
confidence: 99%
“…This finding is similar to those of a mixed study among women of childbearing age from two South-Western States, Nigeria and another study from rural Lagos in which most of the respondents became aware of contraceptive methods from their antenatal clinics. [ 30 31 ] However, this result was contradicted by a community-based study among women of reproductive age in Umuahia, Abia State, in which respondents cited electronic media (television/radio) as their main source of information. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%